트리아졸계 살균제가 크리핑벤트그래스 생육과 토양미생물상에 미치는 영향 - 지재욱(Jae-Uk Jee); 천세철(Se-Chul Chun) (Weed & turfgrass science, 2022)
본 연구는 현장에서 트리아졸계의 살균제를 크리핑 벤트그래스의 여름(생육 쇠퇴기)과 봄 또는 가을철(생육 최성기) 에 사용했을 때 생육억제 효과 정도를 파악하기 위해 실시하였다. 포트 실험에서는 트리아졸계의 살균제 중 크리핑 벤트그래스의 초장 생육억제 효과와 엽색 및 잔디 품질 향상에 메트코나졸 액상수화제와 테부코나졸 액상수화제가 가장우수한 효과를 나타냈다. 포장 실험에선 테부코나졸 액상수화제와 메트코나졸 액상수화제가 봄, 여름 모두 크리핑 벤트그래스의 지상부 생육 억제 및 잔디품질 향상에 비슷한 영향을 미쳤으며, 토양의 진균 개체 수를 억제하는 항균효과를 보여주었다. 하지만 두 약제 모두 트리넥사팍에틸 액제보다 낮은 엽색과 지상부 생육억제 효과를 보여주었다. 포장실험에 사용된 테부코나졸 액상수화제와 메트코나졸 액상수화제는 계절에 관계없이 대체로 농도가 높아질수록 크리핑 벤트그래스의 지상부 생육억제, 엽색 그리고 진균억제에 효과적이었다. This study was conducted to determine the effect of a triazole-based fungicide on growth inhibition when used in the summer (period of growth decline) and spring or autumn (period of active growth) of creeping bentgrass in the field. Among all the fungicides tested in the present study, the metconazole and tebuconazole both as liquid formulation showed the most excellent effects on the plant growth inhibition of creeping bentgrass, and the improvement of leaf color and shoot quality. Also, those two fungicides had similar effects each other on the suppression of shoot growth of creeping bentgrass, on the improvement of turfgrass quality in both spring and summer, and on the antifungal effect suppressing the number of fungi in the soil. However, both fungicides showed less quality of leaf color and less ability to suppress the growth of aboveground parts than those of the trinexapac-ethyl as a liquid formulation. The present study indicated that the tebuconazole and metconazole application in the field were effective on suppressing above the ground growth of creeping bentgrass, on reducing the number of fungi in soil, and on the improvement of leaf color regardless of the season. KCI Citation Count: 0